Treatment Outcome of Liquid Nitrogen (LN) Cryotherapy in Patients Presenting Recalcitrant Alopecia Areata (AA) at Tertiary Care Hospital, Karachi - Arif Sattar Mahar, Rabia Ghafoor, Sagar Kumar, Sonam, Muhammad Ishaque Fayyaaz Cader, Amina Bukhari (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the treatment outcome of liquid nitrogen (LN) cryotherapy in patients presenting with recalcitrant alopecia areata (AA) at tertiary care hospital, Karachi. Material and Methods: This Descriptive study was conducted in the department of Dermatology, JPMC, Karachi. The duration of study was Six months after the approval of synopsis from 15 December 2021, to 14 June 2022. Total 88 patients were included in the study. The patients were assessed for treatment outcome at 8 weeks and were labeled as having excellent, good, moderate, poor and no response. Results: Total 88 patients were included in the study. Mean ± SD of age was 38.3±12.5 years. In distribution of gender, 58 (65.9%) were male while 30 (34.1%) were female. Outcome of liquid nitrogen showed excellent response in 5 (5.7%), good response in 29 (33.0%), moderate 19 (21.6%), poor 9 (10.2%) while no response of liquid nitrogen was noted in 26 (29.5%) patients. Practical implication: The treatment given is mainly for cosmetic reasons and to halt the progression of the disease. Previously, therapeutic outcomes of these treatment options were dealt with in many studies. At the same time, long treatment duration, high cost, invasiveness and inconvenience of application have hindered the utmost treatment outcome and patient satisfaction. Conclusion: It is to be concluded that good response of liquid nitrogen was noted in most of the patients followed by moderate and poor response. More prospective and well-controlled trials are needed to validate the current findings. Keywords: Alopecia Areata, Cryotherapy, Liquid Nitrogen, Prevalence